Stress Analysis in Structural Components of the Koepe Pulley in Hoisting Installations - WOLNY, Stanisław; BADURA, Sławomir (Engineering Transactions, 2014)
Hoisting installations in mines have been constructed and operated for many years, yet they still merit a rigorous research to identify all factors that would enable us to improve their performance parameters. A Koepe pulley in a winding system is a complex structural component, made of plates, shells, discs, membranes, radial or circumferential fin elements varying in their actual layout, depending on the design. The strength analysis of a Koepe pulley in a hoisting system is carried out to get a better insight into the state of stress experienced by pulley components under the operational loads and to find the extreme values of the stress components, which underlies the fatigue endurance and life assessments. Accordingly, the stress analysis of pulley elements is performed by the numerical methods, utilising the FEM approach. Models are developed using the program “FEMAP” and the stress analysis uses the package “NE”/“Nastran for Windows’. The numerical data are then verified through strain (stress) measurements taken on a real object, under the typical operating conditions.